Snorri Sturluson and the Edda : the conversion of cultural capital in medieval Scandinavia - Wanner, Kevin J. (Toronto Old Norse and Icelandic studies., 2008)
Wanner brings us a new account of the interests that motivated the production of the Edda, and resolves the mystery of its genesis by demonstrating the intersection of Snorri's political and cultural concerns and practices.